A clinical study of external ear reconstruction: a study of 20 cases - Katwala, Priyank K.; Pawar, Vishal A.; Katwala, Palak P.; Parmar, Ketan H. (International Surgery Journal, 2019)
Background: Auricular defects pose one of the most difficult challenges in reconstructive surgery of the head and neck. The reason is the unique three-dimensional anatomical architecture of the auricle, with its multiple concavities and convolutions of the cartilage and the thin, delicate skin cover. Acquired auricular deformities commonly result from traumatic injuries, burn trauma or tumour extirpation. These vary in severity from simple lacerations to complete auricular avulsions. Congenital ear deformity (microtia) occurs in every 1 out of 6000 live births. The goal of reconstruction is the precise duplication of the missing anatomical part with regard to size, orientation and anatomical landmarks. Methods: Range from healing by secondary intention to complete replacement with autologous rib cartilage and/or auricular prosthesis. Total auricular reconstruction was done by two methods: (1) Nagata and (2) Brent’s method. Nagata’s technique is commonly performed in this study. The present study aimed to evaluate the reconstruction of auricular defects using autologous rib cartilage graft with or without temperoparietal fascia flap covered by split-thickness skin graft. Results: Excellent cosmetic result can be obtained with adequate skills and training in carving the cartilage for auricular framework. This improves confidence and gives psychological support to microtia patients. Conclusions: With training and method, results in ear reconstruction using autologous rib cartilage are excellent and reproducible.